Diptera communities from Ria de Aveiro saltmarshes, with new records for Portugal - Prado e Castro, Catarina; Carles-Tolrá, Miguel; Santos, Vasco; Ameixa, Olga M.C.C. (Fragmenta entomologica, 2023)
Ria de Aveiro costal lagoon is a socio-ecological system comprising a rich landscape mosaic of beaches, dunes, sandflats, mudflats, seagrasses, and small water channels. The lagoon is one of the largest saltmarsh areas in Portugal and Europe, supporting coastal food webs and serving as a nursery area for several species. For these features Ria de Aveiro is a Long-Term Socio-Ecological Research platform (LTSER) site and integrates the Natura 2000 network. Despite this, only recently research has been conducted regarding its entomofauna. In this study, field collections were carried in seven locations along Ria de Aveiro saltmarshes areas by sweep-netting the dominating halophyte vegetation in September 2020. A total of 222 Diptera specimens from 13 families (Asteiidae, Canacidae, Chamaemyiidae, Chyromyidae, Hybotidae, Lauxaniidae, Milichiidae, Scathophagidae, Sciomyzidae, Sepsidae, Sphaeroceridae, Therevidae and Ulidiidae), belonging to 19 genera and 23 species, are presented in this paper. From these, 1 genus and 4 species are new records for Portuguese territory. Sphaeroceridae was the most species-rich family, with Rachispoda fuscipennis being the most abundant species recorded. This study provides a snapshot into coastal insect communities in Portuguese coastal lagoons and highlights the need to continue to access insect biodiversity in these coastal areas threaten mostly by sea-level rise, coastal squeeze, and salinity.